The fate of fertilizer nitrogen in a high nitrate accumulated agricultural soil - Quan, Zhi; Huang, Bin; Lu, Caiyan; Shi, Yi; Chen, Xin; Zhang, Haiyang; Fang, Yunting (Scientific reports, 2016)
Well-acclimatized nitrifiers in high-nitrate agricultural soils can quickly nitrify NH 4 + into NO 3 − subject to leaching and denitrifying loss. A 120-day incubation experiment was conducted using a greenhouse soil to explore the fates of applied fertilizer N entering into seven soil N pools and to examine if green manure (as ryegrass) co-application can increase immobilization of the applied N into relatively stable N pools and thereby reduce NO 3 − accumulation and loss. We found that 87–92% of the applied 15 N-labelled NH 4 + was rapidly recovered as NO 3 − since day 3 and only 2–4% as microbial biomass and soil organic matter (SOM), while ryegrass co-application significantly decreased its recovery as NO 3 − but enhanced its recovery as SOM (17%) at the end of incubation. The trade-off relationship between 15 N recoveries in microbial biomass and SOM indicated that ryegrass co-application stabilized newly immobilized N via initial microbial uptake and later breakdown. Nevertheless, ryegrass application didn’t decrease soil total NO 3 − accumulation due to its own decay. Our results suggest that green manure co-application can increase immobilization of applied N into stable organic N via microbial turnover, but the quantity and quality of green manure should be well considered to reduce N release from itself.